PEMANFAATAN BIOSAKA DALAM MENDUKUNG PERTANIAN ORGANIK DI DESA KEBON AYU KECAMATAN GERUNG KABUPATEN LOMBOK BARAT: Utilization Of Biosaka In Supporting Organic Agriculture In Kebon Ayu Village, Gerung District, West Lombok District - Zainab, Siti; Haryantini, Baiq Azizah; Sunantra, I Made; Wardhana, Agung Widya; Arifin, Zainal; Baharuddin, Baharuddin; Hidayah, Mirfatul; Apzani, Wawan (Yayasan Al-Amin Qalbu, 2023)
Biosaka is a liquid derived from plant extracts which has an elicitor function for stimulate the plant cells so that plants can grow optimally. Kebon Ayu village is one of the villages that has golden melon agrotourism. However, this village still has a lot of land that is not utilized optimally due to limited capital for production costs for cultivation. Therefore, this activity was carried out with the aim of introducing one of the innovations called biosaka to farmers with the aim of reducing the need for synthetic chemical fertilizers and pesticides in agricultural cultivation activities. The method used in this activity was the delivery of material then followed by a demonstration of making biosaka and application on residents' land. The result of this activity is that the training participants are able to make biosaka and it is hoped that this knowledge can be applied in plant cultivation businesses so as to achieve sustainable organic farming